2022
DOI: 10.1111/os.13546
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Nonunion and Fracture Following Biological Intercalary Reconstruction for Lower‐Extremity Bone Tumors: A Systematic Review and Pooled Analysis

Abstract: Objectives To determine nonunion rate, fracture rate, and their risk factors following biological intercalary reconstruction for lower extremity bone tumors. Methods A systematic review and pooled analysis were conducted. PubMed, Embase, and Wiley Cochrane Library were searched from inception up to June 01, 2020. Studies concerning biological intercalary reconstruction after resection of lower extremity bone tumors were included. Overall nonunion and fracture rates were calculated. For studies reporting patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…However, the shortcomings of biological reconstructions include the risk of disease transmission, delayed rehabilitation, and a relatively high risk of immune rejection, nonunions, infections, and fracture. 5 , 7 , 10 , 18 , 19 According to Ramkumar et al, 20 patients who underwent JSLSS and intercalary allograft had more major complications than those underwent proximal femoral resections with allograft-prosthetic compsite reconstructions. Compared with biological reconstruction, using metallic prostheses shortens the non-weightbearing period and have low incidence of early complications, which is associated with a shorter hospital stay and better quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…However, the shortcomings of biological reconstructions include the risk of disease transmission, delayed rehabilitation, and a relatively high risk of immune rejection, nonunions, infections, and fracture. 5 , 7 , 10 , 18 , 19 According to Ramkumar et al, 20 patients who underwent JSLSS and intercalary allograft had more major complications than those underwent proximal femoral resections with allograft-prosthetic compsite reconstructions. Compared with biological reconstruction, using metallic prostheses shortens the non-weightbearing period and have low incidence of early complications, which is associated with a shorter hospital stay and better quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…The use of allograft for reconstruction after oncologic resection is common but is associated with nonunion rates from 0% to 53% and allograft fracture rates from 0% to 75%. 41 Allograft incorporation remains a challenge. Vercio et al 42 demonstrated excellent union when using a motorized magnetic lengthening nail in compression mode for allograft reconstruction after tumor.…”
Section: Introductionmentioning
confidence: 99%